AB0483 Cutaneous adverse events related to TNFα blockers in patients with chronic inflammatory arthritis. (23rd January 2014) - Machado, N.P.; Pinheiro, M.M.; Reis Neto, E.T.; Melo, M.R.; Pereira, D.F.; Porro, A.; Ciconelli, R.M.
Abstract : Background: TNFα blockers are effective options for the treatment of different forms of chronic inflammatory arthritis (CIA). However, these drugs are associated with a greater frequency of adverse events, especially infectious and allergic events. Objectives: To evaluate the incidence and the main risk factors associated with cutaneous adverse events (CAE) in patients with CIA following anti-TNF therapy. Methods: A total of 257 patients with active CIA and under using TNFα blockers were analyzed – 158 with rheumatoid arthritis (RA), 87 with ankylosing spondylitis(AS) and 12 with psoriatic arthritis (PA) – in a prospective analysis from January 2005 to December 2009. Patients with active or chronic infection, including hepatitis B, hepatitis C or human immunodeficiency virus, and those with overlap of other autoimmune rheumatic diseases were excluded. Anthropometric, socioeconomic, demographic and clinical data were evaluated, including DAS28, BASDAI and PASI. Skin conditions were evaluated by two dermatologists and a biopsy was performed in cases of doubt. Infectious events were classified as viral, parasitic, fungal or bacterial, depending on the clinical condition or identification of the etiological agent. Associations between CAE and clinical, demographic and epidemiological variables were determined using the chi-square test and logistic regression analyses for the identification of risk factors. The level of significance was set at 5% (p<0.05). Results: After 60 months of follow up, 71 CAE (73.85/1000 patients-year) were observed, especially related to allergic and immune-mediated phenomena (37.93/1000 patients-year), followed by infectious conditions (34.71/1000 patients-year), including bacterial (47.1%), parasitic (23.5%), fungal (20.6%) and viral (8.8%). Three CAE (4.22%) were classified as serious. The main risk factors significantly associated with CAE were advanced age (OR=1.09; 95%CI: 1.05-3.72), female gender (OR=2.8; 95%CI: 1.90-5.63), diagnosis of RA (OR=1.9; 95%CI: 1.11-4.62), disease activity [DAS28: OR=1.5; 95%CI: 1.2-4.68 or BASDAI: OR=1.1; 95%CI: 1.02-6.37], use of IFX (OR=1.6; 95%CI: 1.06-4.01), independently from time since diagnosis. These reactions generally had a good prognosis after withdrawal of medications and specific treatment. Conclusions: Our results demonstrate that the skin is an important site affected by adverse reactions following TNFα blockers. References: Smolen JS, Landewé R, Breedveld FC, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs. Ann Rheum Dis 2010; 69: 964-975. van der Heijde D, Sieper J, Maksymowych WP, et al. 2010 Update of the international ASAS recommendations for the use of anti-TNF agents in patients with axial spondyloarthritis. Ann Rheum Dis 2011; 70: 905-911. Ritchlin CT, Kavanaugh A, Gladman DD, et al. Treatment recommendations for psoriatic arthritis. Ann Rheum Dis 2009; 68: 1387-1394. Disclosure of Interest: None Declared